2019
DOI: 10.1371/journal.pone.0206194
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturization and optimization of 384-well compatible RNA sequencing library preparation

Abstract: Preparation of high-quality sequencing libraries is a costly and time-consuming component of metagenomic next generation sequencing (mNGS). While the overall cost of sequencing has dropped significantly over recent years, the reagents needed to prepare sequencing samples are likely to become the dominant expense in the process. Furthermore, libraries prepared by hand are subject to human variability and needless waste due to limitations of manual pipetting volumes. Reduction of reaction volumes, combined with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…RNA sequencing libraries were prepared using a previously described protocol optimized and adapted for miniaturization and automation. 29 Libraries were sequenced on a NovaSeq 6000 machine (Illumina) to generate 150 nucleotide (nt), paired-end reads. Samples were also sequenced after enrichment for EV-A71 and EV-D68 genomes using FLASH (Finding Low Abundance Sequences by Hybridization, Supplemental Table 2).…”
Section: Metagenomic Sequencing Library Preparationmentioning
confidence: 99%
“…RNA sequencing libraries were prepared using a previously described protocol optimized and adapted for miniaturization and automation. 29 Libraries were sequenced on a NovaSeq 6000 machine (Illumina) to generate 150 nucleotide (nt), paired-end reads. Samples were also sequenced after enrichment for EV-A71 and EV-D68 genomes using FLASH (Finding Low Abundance Sequences by Hybridization, Supplemental Table 2).…”
Section: Metagenomic Sequencing Library Preparationmentioning
confidence: 99%
“…26 The latter enabled subsequent bioinformatic assessment of the total RNA mass input in each sample. 27 RNA was then fragmented and subjected to a modified metagenomic spiked sequencing primer enrichment (MSSPE) library preparation method. 28 Briefly, a 1:1 mixture of the NEBNext Ultra II RNAseq Library Prep (New England Biolabs) random primer stock and a pool of SARS-CoV-2 primers at 100 µM was used at the first strand synthesis step of the standard RNAseq library preparation protocol to enrich for the recovery of reads spanning the length of the SARS-CoV-2 genome sequence in the context of mNGS analysis.…”
Section: Respiratory Virus Detection By Metagenomic Sequencingmentioning
confidence: 99%
“…Researchers may also decrease the cost through reducing library preparation reaction volumes, as this is typically the most costly step in NGS preparation (Table S10). While reducing reaction volumes deviates from the formulations validated by manufacturers, many researchers (including ourselves) have used half-reactions for preparing NGS libraries with no noticeable effect on quality, and other studies have reported reliable library preparation down to one-sixteenth reactions (4447).…”
Section: Discussionmentioning
confidence: 99%